EXTH-18. DEVELOPMENT OF ULTRASOUND-FACILITATED DRUG DELIVERY DEVICE FOR LOCAL DRUG INFUSION AGAINST BRAIN TUMORS. (5th November 2018) - Saito, Ryuta; Sato, Aya; Inoue, Kenji; Jia, Wenting; Okuno, Saori; Ohashi, Yuji; Kamada, Kei; Yoshikawa, Akira; Tominaga, Teiji
Abstract: OBJECT: Drug delivery against brain tumors is a challenge. Blood-brain barrier (BBB) and blood-tumor barrier always hinders the entry of therapeutic agents into brain tumors. On the other hand, local drug delivery also faces a major problem: limitations of distribution. Convection-enhanced delivery (CED) is a promising drug delivery method that deliver high-concentration drug directly into the targeted lesion beyond the BBB. We have been working to develop a novel treatment strategy with CED delivering chemotherapeutic agents directly into the tumor. Previously we developed an ultrasound facilitated drug delivery (UFD) system in order to achieve more robust drug distribution (J Neurosurg 124, 2016). In this study, we fabricated a second-generation device by analyzing optimal ultrasound generating condition and tested the intraparenchymal drug distribution using the device. METHODS: Resonance frequency of the device was determined by measuring the strength of sound field using hydrophone in water. Using the UFD system, applying resonance frequency, evans blue dye was infused into the striatum of Fisher344 rats. Immediately after the infusion, brains were harvested, quickly frozen, and sectioned to evaluate the distributions of the dye. RESULTS: The second-generation device successfully distributed the dye to the volume 1.5~2 times larger than simple CED with using half the driving voltage than first-generation device. Moreover, the distribution instability, which was a major problem with the first-generation device, was resolved achieving smaller standard deviation. Using multiple resonance frequencies of the device, we found the difference in drug distribution; suggesting the existence of optimal frequencies for brain interstitial drug delivery. CONCLUSIONS: The second generation UFD device successfully and stably achieved enlarged distribution in the brain parenchyma.